Consumption Pattern Counseling About “Anti Hypertension and Anti Diabetes” and Exercise for the Elderly to Avoid Hypertension in Tenaru Village - Rahmawati, Arsya; Madani, Anan; Rohmawati, Karima (Journal of Health Community Service, 2024)
The aging process as an accumulation of damage at the cellular and molecular levels that occurs over a long period of time is often associated with the occurrence of noncommunicable diseases. Various studies have shown that age is one of the risk factors for non-communicable diseases, such as those often experienced by the elderly, namely hypertension and diabetes. Implementation methodhealth promotion to the community, especially vulnerable communities such as the elderly through blood pressure checks and Random Blood Sugar (GDA) tests and also providing counseling on consumption patterns about "Anti-Hypertension and Anti-Diabetes" and Elderly Exercise to Avoid Hypertension which was carried out at the Tenaru Village Hall.after the elderly have been done, they already know a little about the symptoms and what can cause high blood pressure. In addition, KKN Group 14 students of Nahdlatul Ulama University Surabaya also provide education on elderly exercise to avoid hypertension and village midwives also provide medication to reduce symptoms of hypertension and lower blood pressure.The community (elderly) participated in attending counseling, exercise, and also tests that had been created by UNUSA KKN Group 14 to prevent hypertension or diabetes.